Environmental and Social Impacts of Urbanization: Strategies for Achieving Sustainable Development - Afaz, Triyanchy; Afkar, Afkar; Syah, Nurhasan; Heldi, Heldi; Catri, Indra; Gusman, Mulya (Science and Environmental Journal for Postgraduate, 2024)
Urbanization has significantly increased alongside economic growth and social change, bringing both opportunities and challenges, particularly in environmental and social contexts. This study aims to analyze the environmental and social impacts of urbanization in relation to sustainable development, using a comprehensive literature review of 50 relevant articles published between 2019 and 2024. The analysis focused on two main themes: the environmental and social consequences of urbanization and strategies for achieving sustainability. The results reveal that urbanization contributes positively to economic growth, access to education, and healthcare, but negatively impacts the environment and social equity. Key challenges include pollution, waste generation, climate change, limited affordable housing, and social inequalities. Notable strategies for sustainable urbanization include effective waste management, clean energy adoption, and green city initiatives. Research from Jambi and Serang highlights community involvement in waste reduction and the promotion of renewable energy as vital components for urban sustainability. The study concludes that sustainable urban planning, emphasizing integrated solutions across environmental, economic, and social domains, is crucial for mitigating urbanization's negative impacts. Collaborative efforts among policymakers, local communities, and researchers are essential to create inclusive and resilient cities aligned with sustainable development goals.